Kirke-Klokken 1845 - Rønne, Karl (Grundtvig-studier, 1970)
“ The Church Bell” By Karl Rønne Continuing the protracted and varied debate on “ Kirke-Klokke” (“ Church Bell” ) (see H. Toldberg, Gr.-St. 1961 ) this essay sets out to show that the form, as it appeared in 1845, has a carefully planned structure and a definite purpose in the debate of that time.The hymn, or poem, first confronts hymn writing (symbolically expressed in “ Kirke-Klokke” ) with secular literature: deeply felt, highly emotional (“ædle malme (precious metals) st. 1 ) recognised, well-reputed (“til Hovedstæder” (for capitals) st. 2 ), and stylistically pure, technically correct poetry (“ Strengeleg” (lyre) st. 3 ). The hymn does not belong with any of these modes; it evokes response among the humble, the unimpressive, in lowly places, (“den lille By” (the little village)).The poet now considers which kind af hymn writing should be regarded as highest in rank (“ Rangen” ). The hymns of Christmas and Easter are considered (st. 4- 5 ), but in st. 6 the evening song, in a revulsion to the poet’s personal (“for mig” (for me)) present situation (“nu” (now)), seems to win the leading place. He cannot pledge himself to Christmas and Easter as they appear in his childhood memories (“ Landet” (the country/land) = the land of his childhood), and he is a stranger in life (“ Har hjemme selv jeg veed ei hvor” (I do not know where I belong)). The evening song of harvest time, where the Creator (“ Himmelrøsten” (the voice from Heaven)) calls home his hoary servant after he has completed his lifework at the evening of his life, wins “ Rangen” (the pride of place), as it has the message: Han sov hen som Soel i Høst gaar ned! (He passed away in the same way as the sun sets in autumn).